Pre-Service English Teachers’ Perception on Blended Learning Model During Covid-19 Pandemic - Sunra, La (Celebes Journal of Language Studies, 2023)
This study was conducted to find out pre-service English teachers’ perceptions of the blended learning model during the Covid-19 pandemic. A descriptive quantitative method was applied in this research. The population was pre-service English teachers at the State University of Makassar who did teaching practicum on the KKN program (Student Study Service) during 2020/2021. There were 30 pre-service English teachers that participated by using random sampling. The data was collected through a Google form questionnaire with Likert Scale. The results showed the average with a score of 3,27 can be interpreted that the pre-service English teachers’ perception of Blended Learning during the Covid-19 pandemic is positive but not at a high level.